The Intention to Use Mobile Payment during the Covid-19 Pandemic: The Mediating Role of Attitude - Handayati, Puji; Trisnawati, Novi (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2023)
The Covid-19 pandemic requires individuals to maintain physical distance and this has affected buying and selling transactions where previously the majority used the cash payment system to switch to digital payments or mobile payments to maintain distance and reduce physical contact. This study aims to examine the effect of perceived usefulness and perceived ease of use on the intention to use mobile payment in Malang of Indonesia. This study also investigates the mediating role of attitude in explaining this relationship. The population in this study are individuals who adopted mobile payment services in Malang of East Java in Indonesia. The analytical tool used is Structural Equation Modeling (SEM). The findings of this research showed that perceived usefulness and perceived ease of use had a direct effect on attitudes, perceived usefulness, while perceived ease of use and attitudes also had a direct effect on the intention to use mobile payment. In addition, attitudes can mediate perceived usefulness and perceived ease of use on the intention of using mobile payments during the Covid-19 pandemic.